Shaking table test on 1000 kV UHV transmission tower-line coupling system. (October 2020) - Liang, Huangbin; Xie, Qiang; Bu, Xianghang; Cao, Yongxing
Abstract: Ultra high voltage (UHV) transmission tower-line coupling system consists of transmission lines (conductors and ground wires) supported by a series of lattice towers. However, in the current seismic design code, the transmission lines are just simplified as additional mass while the effect of nonlinear vibration of transmission lines on the seismic responses of transmission towers is not taken into consideration. To analyze the influence of the ignorance of the coupling effect between towers and transmission lines, two types of model structures, i.e. tower-line coupling system model and single tower model with lumped masses, should be tested for comparison. But normal reduced-scale model design method cannot complete the shaking table test by a uniform geometric similarity ratio for the coupling system in the limit of table size, hence this paper proposed to rescale the geometric similarity ratio for the model design of transmission lines and meanwhile satisfied the requirement in dynamic properties similitude and inertia force similitude separately, which successfully solved the problem that the span of transmission lines in the test was too large to fit within the shaking table. This method may offer reference to experimental studies for other large-span structures and the experimental results show that the nonlinear vibration of transmission lines plays a role as seismic reduction by dissipating some seismic energy to towers under earthquake.